BOOK REVIEW: Ora Kwo (ed.) (2010). Teachers as Learners: Critical Discourse on Challenges & Opportunities. Springer & CERC, Hong Kong. - HALASZ, Gabor (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
It is important to take a special note of the context in which this book was born. As the foreword and the introductory chapter stress it emerged from the 49th World Assembly of the International Council on Education for Teaching organised in the city of Hong Kong with the theme of “Teachers as Learners: Building Communities for Professional Development”. Both the supporting organisation and the locality are important. The International Council on Education for Teaching (ICET), founded in 1953, is probably the oldest and most “robust” global organisation involved in teacher education (Dolby-Rahman, 2008), and its yearly conferences have had a significant impact on the development of the area. As for the venue: there were, in the time of the birth of the chapters of the book, two particularly important ingredients in the Hong Kong education policy context that deserve mention as they seem to be directly linked with the key message the of the book: (1) the focus of the education reform on learning and learners and (2) the dynamics of educational innovation.